Pemetaan Potensi Pajak Reklame Menggunakan K-Means WebGIS - Silaban, Ema Deloris; Sitorus, Paniel Sam P.; Manalu, Dudes (KAKIFIKOM (Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer), 2026)
Purpose: This study develops a Web GIS-based advertisement tax potential mapping system using K-Means Clustering at the Regional Financial and Revenue Management Agency of Simalungun Regency, with Bandar District as the case study. Design/methods/approach: The study applies Research and Development with the Waterfall model through requirements analysis, system design, implementation, and testing. The system uses PHP Native, MySQL, Leaflet.js, latitude, longitude, and nominal tax value. K-Means with k=3 and Euclidean Distance groups advertisement objects into high, medium, and low potential categories. Findings/results: The system processed 150 advertisement tax records and produced three clusters: 3 high-potential objects, 18 medium-potential objects, and 129 low-potential objects. The process converged at the third iteration. Manual calculation and PHP output showed 100% conformity, and black-box testing confirmed that the main system features worked properly. Conclusions: The proposed system converts conventional tabular records into interactive geospatial information that helps officers prioritize advertisement tax supervision more objectively.